О возможности воспроизведения прямоугольного управляющего импульса электромагнитным вибровозбудителем - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
On the basis of the singularis expansion of a jump-like function, the possibility to reproduce a rectangular pulse with the help of an electromagnetic vibroexciter is investigated.